Black Phosphorus Q-Switched Large-Mode-Area Tm-Doped Fiber Laser - Yan Ren; Zhipeng Qin; Guoqiang Xie; Zhen Qiao; Jingui Ma; Peng Yuan; Liejia Qian; Shikai Wang; Chunlei Yu; Lili Hu (International Journal of Optics)
We report on a passively Q-switched fiber laser with black phosphorus as saturable absorber. By employing the sol-gel fabricated large-mode-area Tm-doped fiber as gain medium, a high-energy Q-switched fiber laser has been demonstrated which delivers the maximum pulse energy of 11.72 μJ with the pulse width of 660 ns at the wavelength of 1954 nm. Our experimental results indicate that BP Q-switched large-mode-area Tm-doped fiber laser is an effective and reliable approach to generate high-energy pulses at 2 μm.